Analisis Strategi Pemasaran Syariah dalam Meningkatkan Penjualan pada Depot Air Minum Isi Ulang Water Zone - Aditya Arbi; Mellya Embun Baining; Rohana Rohana (Jurnal Penelitian Ilmu Ekonomi dan Keuangan Syariah, 2024)
Drinking water according to the Regulation of the Minister of Health of the Republic of Indonesia No. 492/Menkes/per/IV/2010 is water that has been processed or unprocessed, which meets health requirements and can be directly consumed by humans. In simple terms, drinking water goes through a gradual process to become drinkable. This study uses a descriptive qualitative research design. Qualitative methods, according to Meleong, are research techniques that produce descriptive data from people and actions that can be seen from written or spoken language. According to Kountur, this type of research focuses on describing a condition or situation as clearly as possible without assessing the research subjects. The results of this study are a description of information from the findings of researchers in the field that are real and factual. Researchers conducted a survey to the research location by means of interviews, documentation and observation of research subjects that had been determined by informants in this study. In its implementation, the Water Zone Refill Drinking Water Depot is a characteristic of Sharia Marketing, including. Theistic, Ethical, Realistic, HumanisticBased on the results of the research that has been conducted on the sharia marketing strategy carried out by the Water Zone Refill Drinking Water Depot, it can be concluded that: The Sharia Marketing Strategy that has been carried out by the Drinking Water Depot turns out to include sharia marketing, namely Theistic, Ethical, Realistic, Humanistic. Sharia marketing constraints include less than optimal marketing strategies, Tight competition among businesses, Low human resources. Solutions to sharia marketing constraints that have implications for increasing sales Changing the way of thinking from negative to positive. This is done in order to always be confident and optimistic in facing problems.